1999
DOI: 10.1164/ajrccm.159.3.9709090
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ventilator Flow Rate on Respiratory Timing in Normal Humans

Abstract: Respiratory rate (RR) increases as a function of ventilator flow rate (V). We wished to determine whether this is due to a decrease in neural inspiratory time (T In), neural expiratory time (TEn), or both. To accomplish this, we ventilated 15 normal subjects in the assist, volume cycled mode. Ventilator flow rate was varied at random, at four breaths with each step, over the flow range from 0.8 (Vmin) to 2.5 (Vmax) L/s. V T was kept constant. The pressure developed by respiratory muscles (Pmus) was calculated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(35 citation statements)
references
References 36 publications
2
32
1
Order By: Relevance
“…Thus we feel that the failure to demonstrate a reduction in TI during T assist with flow assist alone probably reflects the lower level of assist both early (since E assist did decrease TI) and over the entire breath (since combined assist of greater magnitude shortened TI in our previous study). Much larger steady-state increases in inspiratory flow in mechanically ventilated subjects also shorten TI (6,16,20). The results of the present study indicate that more subtle changes in inspiratory flow may also modulate the timing of inspiratory efforts on a breath-bybreath basis if the assist is given early during inspiration.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Thus we feel that the failure to demonstrate a reduction in TI during T assist with flow assist alone probably reflects the lower level of assist both early (since E assist did decrease TI) and over the entire breath (since combined assist of greater magnitude shortened TI in our previous study). Much larger steady-state increases in inspiratory flow in mechanically ventilated subjects also shorten TI (6,16,20). The results of the present study indicate that more subtle changes in inspiratory flow may also modulate the timing of inspiratory efforts on a breath-bybreath basis if the assist is given early during inspiration.…”
Section: Discussionmentioning
confidence: 49%
“…The reduction in TI is probably reflex in origin, and the afferent information is probably carried by the vagus nerve. Previous studies of steady-state increases in inspiratory flow demonstrated a decrease in TI (6) and an increase in respiratory rate during mechanical ventilation that was not affected by breathing route (oral or nasal) or upper airway anesthesia. This suggests that at least some of the receptors mediating the flow-related responses are located in the lungs or chest wall (9).…”
Section: Discussionmentioning
confidence: 79%
“…flow or time cycled) are the most clinically used assisted mode of NIV [5]. Pressure support ventilation (PSV), for example, applies a constant level of positive airway pressure during spontaneous inspiratory efforts; the patient is not a "passive" part of the process, but may respond to the changes in ventilator settings via chemical, mechanoreceptor reflex and behavioural feedback systems [6][7][8].…”
mentioning
confidence: 99%
“…The animals in our study, however, were monitored by flow and airway pressure waves. Alterations in airway pressure and flow waves suggest inspiratory efforts during MV, and have been show to coincide with electromyographic analysis 30 . Uniform airway pressure and flow waves analyzed by the ventilator display, together with the consistence of the respiratory frequency set by the investigator, indicate that passive ventilation was in fact achieved.…”
Section: Analysis Of Experimental Designmentioning
confidence: 85%